Functional Outcome of Metacarpal Fractures Managed by Internal Fixation with Miniplate and Screws: A Cross-Sectional Study - Thapa, Santosh; Singh, Dhiraj; Shrestha, Oshan; Rajthala, Ashish; Jha, Ranjib Kumar (Journal of Nobel Medical College, 2024)
Background: Metacarpal fractures account for up to 40% of all hand fractures. This is commonly encountered among the general population, labour workers, and sportsmen. The appropriateness of the intervention in such cases becomes very important for treatment, rehabilitation, and an early return to work. The objective of this single-centre prospective study is to assess the outcomes of mini-plates and screws in the management of metacarpal shaft fractures. Materials and Methods: This study was conducted among patients with metacarpal fractures. Ethical clearance was obtained before the commencement. This study included the patients that presented to the institution and got operated on from May 19, 2023, to May18, 2024. The primary outcomes of this study were range of motion and quick disabilities of the arm, shoulder and hand (quick DASH) score. The data was analysed using the SPSS 20 software. Results: A total of 22 patients met the inclusion criteria, out of which 14 were males and eight were females. The mean age of patients was 30.22 ± 8.93 years, and the most commonly affected digit was the middle finger (31.8%), commonly affected hand was the right hand (63.6%), and the most common mechanism of injury was fall (45.5%). Range of motion and quick disabilities of the arm, shoulder and hand (quick DASH) score improved significantly at six months when compared to those at three months. Conclusion: Mini-plate and screws are effective methods of managing metacarpal fractures. It can be employed for good functional outcomes and fewer complications.